Influence of Color Psychology on Consumer Behavior among Business Students - Niere, Marvin Ian; Bustamante, John Reno B.; Bacaltos, Maureen S.; Arceo, Ray Angelo B.; Bigno, Hadassah (Future Science / FSH-PH Publications, 2024)
Neuromarketing, a rapidly expanding field, utilizes brain-based techniques to understand and shape consumer behavior. Recently, there has been a surge in the popularity of neuromarketing techniques, supported by research indicating their substantial impact on consumer behavior. Notably, color psychology has emerged as a prominent area within neuromarketing. This study aimed to investigate the relationship between color psychology and its impact on consumer behavior among business students of a university in Cebu City. A quantitative correlational approach was employed, and data were collected from business students responding to Likert survey questionnaires distributed electronically. To achieve the study objectives, descriptive analysis and Pearson's Correlation Coefficient were used to ensure a comprehensive evaluation of the data. The findings revealed a high level of awareness among the respondents, with